2017
DOI: 10.1093/aob/mcx127
|View full text |Cite
|
Sign up to set email alerts
|

Root hairs increase rhizosphere extension and carbon input to soil

Abstract: Root hairs increase exudation and spatial rhizosphere extension, which probably enhance rhizosphere interactions and nutrient cycling in larger soil volumes. Root hairs may therefore be beneficial to plants under nutrient-limiting conditions. The greater C allocation below ground in the presence of root hairs may additionally foster C sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 38 publications
3
94
0
Order By: Relevance
“…Contrasting root phenotypes may have differences in root exudate localization and oxygen availability, two factors that have important effects on the composition and function of root‐associated microorganisms (Hinsinger, Bengough, Vetterlein, & Young, ; Neumann & Römheld, ). The distribution and localization of root exudates and the effect of root architecture and anatomy on carbon rhizodeposition and rhizosphere oxygen content remain unclear (Walker, Bais, Grotewold, & Vivanco, ; Zhalnina et al, ), although recent research indicates that in addition to root tips, root zones coated with root hairs are zones of active carbon rhizodeposition (Holz, Zarebanadkouki, Kuzyakov, Pausch, & Carminati, ). Contrasting root phenotypes are expected to offer contrasting environments for soil microbes recruited to the rhizosphere, rhizoplane, and cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting root phenotypes may have differences in root exudate localization and oxygen availability, two factors that have important effects on the composition and function of root‐associated microorganisms (Hinsinger, Bengough, Vetterlein, & Young, ; Neumann & Römheld, ). The distribution and localization of root exudates and the effect of root architecture and anatomy on carbon rhizodeposition and rhizosphere oxygen content remain unclear (Walker, Bais, Grotewold, & Vivanco, ; Zhalnina et al, ), although recent research indicates that in addition to root tips, root zones coated with root hairs are zones of active carbon rhizodeposition (Holz, Zarebanadkouki, Kuzyakov, Pausch, & Carminati, ). Contrasting root phenotypes are expected to offer contrasting environments for soil microbes recruited to the rhizosphere, rhizoplane, and cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The priming effect of the root on microbial soil communities has been well described (Huo et al, 2017), and we hypothesize that, similarly in our experiments, differences in root morphology and/or root exudates and rhizodeposits primed the observed shifts in fungal communities under P-replete vs P-deprived conditions. Plants respond to P scarcity by remodeling their root system (Williamson et al, 2001;Nacry et al, 2005), which is likely to redefine fungal niches in the root and the rhizosphere by altering the root surface area and the amount of C exuded by the roots (Holz et al, 2018). More specific plant responses to P scarcity include the accumulation of sugars and primary metabolites, and the production of compounds with antimicrobial activity, such as glucosinolates and flavonoids (Pant et al, 2015;Hiruma et al, 2016), which are all likely to affect plant-microbiota interactions (Badri et al, 2009;Bressan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the rhizosphere affected by mucilage (0.6 mm) was smaller compared to results obtained from 14 C imaging analyses. Holz et al (2017) showed that overall root exudates diffused up to 1 mm into the bulk soil. The fact that mucilage did not move as far from the root surface as compared to overall exudates may be explained by the higher viscosity of mucilage compared to root exudates (Read and Gregory, 1997) and reduced diffusion coefficient of mucilage compared to root exudates.…”
Section: Discussionmentioning
confidence: 99%